Relation between isovolumic relaxation period of left ventricle and pulmonary artery pressure in d-transposition of the great arteries. - Bourlon, F (1980)
The study aimed to identify the best echocardiographic time interval (systolic or diastolic) for assessing pulmonary artery pressure in children with d-transposition of the great arteries. Echocardiograms were performed in 21 children with d-transposition of the great arteries within 48 hours of cardiac catheterisation. None of the children had had a Mustard procedure. Twenty-four recordings were obtained, three patients having been catheterised twice. Highest correlations were found for the ratio of the isovolumic relaxation time over the ejection time of the left ventricle (IRT/LVET) to the systolic pressure in the pulmonary artery and also between IRT/LVET and the difference between mean pulmonary artery pressure and mean left atrial pressure. All patients with a negative IRT/LVET ratio had a pulmonary systolic pressure lower than 35 mmHg and a mean pulmonary pressure lower than 25 mmHg. In patients with d-transposition, a negative IRT/LVET ratio appears to be a reliable indication of normal pressure in the pulmonary circulation. Serial echocardiographic studies for the follow-up of patients with d-transposition should include measurement of the time of relaxation of the left ventricle.